Determinación de la tasa de conversión de embriones somáticos del clon promisorio de piñón (Jatropha curcas L.) CP0 52. - Pazmiño González, Gabriela Estefanía (2015)
The aim of this study was to determine the rate of conversion of somatic embryos of promising clone piñón (Jatropha curcas L.) CP 052 INIAP, through the formation of embryogenic callus and regeneration thereof under temporary immersion systems automated (RITA®). The research was conducted in three phases; the first call induction phase began with the disinfection of leaves of adult plants during this phase 11 media culture were tested with different hormone combinations of BAP, kinetin, IBA and IAA. Upon completion of this phase a protocol for indirect induction of somatic embryos was established from leaves for accession CP052, with medium composed 11.42uM AIA + 146.87uM BAP, as the latter gave way to the formation of embryogenic callus and large size organogenic and compact consistency, as well as green-yellow coloring, plus this stage was crucial to choose the best treatments for the next phase, so choosing the J9, J10, J11 treatments. For the second phase or regeneration, he departed from the morphogenic calluses best (J9) of the first induction phase and they were placed in semi solid medium with half of its concentration, 30 g/l of sugar, 0.203 mg/l of IBA, 0.23 mg/l of KIN, 1.84 mg/l of adenine sulfate and 7g/l of agar. Later embryogenic calli from the preceding stage were placed in containers RITA®. Culture medium was tested with two immersion frequency (every 12 and 24 hours) for 30 and 60 seconds respectively. Upon completion of the evaluation, it was observed that exposure of embryogenic callus frequency of 12 hours per 30 seconds, significantly increases the number of embryos with an average of embryos in globular state (1.99), embryos acorazonado state (1.24) and shoots organogenics (3.21). Finally in phase conversion of somatic embryos it proceeded to introduce embryos in germination media a total of six embryos, however, no positive response was obtained. In addition to not having sufficiently representative data to apply an experimental design, this was not done.